A hybrid framework to model factors affecting construction labour productivity: Case study of Iran. Issue 3 (7th October 2019) - Parchami Jalal, Majid; Shoar, Shahab
Abstract : Purpose: This paper aims to model different causal relations among factors interacting with labour productivity in order to recognize the most important factors influencing and influenced by it. Design/methodology/approach: Top 60 factors affecting labour productivity were determined and grouped into 5 major groups by reviewing previous research and interviewing relevant experts. The interactions of factors were modelled using system dynamics (SD) approach. The resulting causal loop diagrams obtained from SD were then applied for identifying the most crucial factors influencing and influenced by labour productivity through the decision-making trial and evaluation laboratory (DEMATEL) method. The impact of factors on each other was finally determined based on the opinions of 63 experts selected from the Iranian construction industry. Findings: The results indicated that factors such as fatigue, lack of labour motivation and lack of skill are the most influencing, and factors such as schedule delay and inflation in the cost of execution are the most influenced by labour productivity. In the end, a set of recommendations to improve construction labour productivity was also presented. Originality/value: The main contribution of the study is proposing a novel method which is capable of providing insights into how causes and effects of construction labour productivity are interrelated. Furthermore, the proposed method makes this study distinct from previous research in the light of prioritizing factors and offering recommendations according to the interrelationships among factors.